Chronic lymphatic leukaemia and engine exhausts, fresh wood, and DDT: a case-referent study. Issue 1 (January 1988) - Flodin, U; Fredriksson, M; Persson, B; Axelson, O
Abstract : The effect of potential risk factors for chronic lymphatic leukaemia was evaluated in a case-referent study encompassing 111 cases and 431 randomised referents, all alive. Information on exposure was obtained by questionnaires posted to the subjects. Crude rate ratios were increased for occupational exposure to solvents. DDT, engine exhausts, fresh wood (lumberjacks, paper pulp workers, and sawmill workers, for example) and also in farming. Further analysis of the material by means of the Miettinen confounder score technique reduced the number of rate ratios significantly exceeding unity to encompass only occupational exposure to engine exhaust, fresh wood, DDT, and contact with horses.